Analise dos empreendimentos e perfil dos empreendedores da microrregião do Seridó Ocidental - Santos, Arthur Cleiton de Medeiros (Universidade Federal Rural do Semi-Árido, 2020)
Nowadays, Brazil's growth in the entrepreneurship sector is notorious due to increasing unemployment, and a key point is the medium and small cities, which is where we can find a high number of companies and entrepreneurs motivated to grow and stand out - on the market. The capitalist system that is based on the current economy has become the competitive and exclusive market, so that the individual to succeed stands out and generates a good service to society. Economic development, the course of the work the objective is to diagnose the enterprises and analyze the profile of the entrepreneurs of the micro-region of Seridó Ocidental - RN. The methodology, the bibliographic research of quantitative, exploratory and descriptive characteristics, distribution by gender in the labor market, level of education, type of enterprise, lifespan of companies, among other characteristics, were applied for the development of the work. It was clear that the majority of entrepreneurs are male and the predominance, when it comes to the age of business, is the 6- to 10-year-old enterprises, which young people are undertaking at an earlier age, than most entrepreneurs aged between 21 - 50 years old, the majority of whom have only high school education, the majority of entrepreneurs who wish to make improvements in the future or even open another business, entrepreneurs as a whole do not resort much to public loans. The present study points to a certain development of the surveyed micro-region.
Monografia
Keywords: Empreendimentos; Desenvolver; Empresas; Negócios; Companies; Development; Interprise; Business; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA